IMPROVING WRITING ABILITY OF ELEMENTARY SCHOOL STUDENTS BY USING THE HANDS ON ACTIVITY METHOD - Ruli Setiyadi; Yosi Indriastuti (IKIP Siliwangi Bandung, 2019)
The study entitled Improving the Writing Ability of Elementary School Students by Using the Hands on Activity Method was motivated by the low ability to write students at the Elementary School level. The purpose of this study is to improve writing skills in elementary school students. The use of the method in this study is Classroom Action Research as much as two cycles to maximize student learning outcomes in writing skills. The results of this study are the increasing ability to write elementary school students which is indicated by the value of learning outcomes above the KKM standard. In addition, the results of this study also revealed that the Hands on Activity method can improve students' writing abilities and have a good impact on learning Indonesian in Elementary Schools.